Investigation Progress on Integration of Forming and Modification in Extrusion for Light Alloys - WANG Ye; LI Feng; WANG Yu; WANG Yanpeng (Journal of Harbin University of Science and Technology)
Extrusion processes can exert technical characteristics and integration advantages in preparing and forming lightweight highperformance magnesium alloys. The lightweight alloy extrusion integration consisting of forming and modification emerged as the times require, and has gradually become one of the hot topics in extrusion field. The technical characteristics of above processes are that the previous independent fine grain preparation processes is skillfully integrated into the extrusion processes through optimizing extrusion dies, changing loading modes and adjusting the structure of billets, etc. The actual effects of “shapes/properties” dual control of extrusion products have been achieved in a single pass. It can be seen from the microcosm of the research overviews that compared with the conventional extrusion, its comprehensive advantages are reflected in many aspects such as reducing forming load, improving the uniformity of extrusion flow, and improving the microstructure properties of the extruded products. To solve the related basic scientific problems, it provides scientific guidance for the research and application of lightweight highperformance alloy in short process and dual control of shape/performance.